Sheep in the Skin of a Wolf, An Unusual Sub-retinal Lesion - Muhammad Khalil, Afzal Hussain, Tayyaba Gul Malik (Pakistan Journal of Ophthalmology, 2015)
Purpose: To describe a case of sub retinal hemorrhage mimicking as uveal tumour. Material and Methods: Although new diagnostic techniques are emerging every now and then, indirect ophthalmoscopy is still a gold standard in the diagnosis of retino-choroidal lesions. Problems arise when media is not clear. OCT, FFA are not possible in hazy media and fine needle aspiration cytology carries a risk of seeding. There are other conditions like choroidal naevi, choroidal hemangiomas and hemorrhages which can observed, but when it comes to choroidal melanoma, it becomes very important to diagnose it in time to prevent metastatic complication and death. A case of an 81 years old male is presented who had vitreous hemorrhage and a sub retinal mass. Age of the patient, size of the mass and B scan were quite confusing to exclude a choroidal malignancy. Pars plana vitrectomy was performed and the mass proved to be a sub retinal hemorrhage secondary to exudative age – related macular degeneration. Key Words: Choroidal melanoma, sub retinal hemorrhage, Intra gel hemorrhage, choroidal lymphoma, choroidal metastasis, choroidal naevus.